Famous Hyperboreans - Sandin, Pär (Nordlit, 2014)
The individual Hyperboreans appearing in ancient literature are presented with a review of the Greek and Latin sources and collections of references. Most of the mythological characters are briefly discussed, but the literary evolution of the legends of Abaris and of the “Hyperborean maidens” are treated in some detail. Some of the literary sources receive scholarly treatment, the paper including philological notes on [Aristeas Epic.] fr. 11 Bernabé (the passage is inspired by an interpretation of the name Abaris); Call. Dian. 204–5 (includes an allusion to the Hyperborean maiden Upis/Opis); Call. Del. 293–95 (the passage hints at an etymology of the word Περφερέες; and ἐκεῖνοι in 295 is sound); Call. Aet. fr. 186.26–30 Pfeiffer (discussion of the myth of Orion and Opis); D.H. 1.43.1–2 (discussion of the myth of Palantho and Heracles); Hecat.Abd. FGrH 264 frr. 7, 12 (discussion of the different information about the Hyperborean leadership that is given in the two fragments); Hdt. 4.35 (interpretation of the phrase ἅμα αὐτοῖσι τοῖσι θεοῖσι); Iambl. VH 32.217 (the stated opinions of Abaris seem similar to those professed in Heraclid.Pont. fr. 75 Wehrli); Verg. Aen. 11.857–58 (the utterance of Opis alludes to the death of Orion as presented in Euphorion, Callimachus and pseudo-Apollodorus).